2015
DOI: 10.1007/s11205-015-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Financial Crisis Experiences

Abstract: Using eight annual household surveys for the Netherlands between 2006 and 2013, we find that respondents' personal adverse financial crisis experiences do not only reduce their trust in banks, but also have an immediate negative effect on generalized trust. Respondents who were customers of a bank that ran into problems have less trust in banks than respondents without this experience. Respondents who were customer of a bank that failed have a significantly stronger decline of generalized trust than other resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 45 publications
0
30
0
2
Order By: Relevance
“…Simply the fact that individual wellbeing is positively correlated with social trust suggests that, as economic crises decrease wellbeing, this also translates into declining social trust, whatever the causal relation. There is also evidence suggesting that social trust is affected by one's own negative experiences and, therefore, it declines during a crisis (van der Cruijsen et al 2016). However, some scepticism regarding this finding can also be found in the literature.…”
Section: Social and Institutional Trust During An Economic Crisismentioning
confidence: 99%
“…Simply the fact that individual wellbeing is positively correlated with social trust suggests that, as economic crises decrease wellbeing, this also translates into declining social trust, whatever the causal relation. There is also evidence suggesting that social trust is affected by one's own negative experiences and, therefore, it declines during a crisis (van der Cruijsen et al 2016). However, some scepticism regarding this finding can also be found in the literature.…”
Section: Social and Institutional Trust During An Economic Crisismentioning
confidence: 99%
“…However, there is little research on the direct consequences of suffering the effects of the economic crisis on generalized trust. The few studies that exist have shown that adverse personal experiences related to the financial crisis contribute to reducing generalized trust ( van der Cruijsen et al, 2016 ). Indeed, groups confront one another when resources seem to be scarce, and as a likely result, they trust each other less ( Fiske et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trust in other people is higher for females than males and positively related to homeownership, which is a rough proxy for wealth. Van der Cruijsen et al (2012) find the later effects as well for the Netherlands. Last, trust in other people is higher for people who are 34 years or younger than for people belonging to older age classes.…”
Section: Regression Methodsmentioning
confidence: 71%